Analysis Inventory For Supporting Materials In Nickel Industry Using Material Requirement Planning Method - Tola, Alimuddin; Vanany, Iwan (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
Nickel is one of the resources that is often used by humans with its use increasing from each year. In order to increase nickel production, an integrated and optimum system is needed with carrying out the production and business processes in the one of Indonessian nickel company. To achieve the objectives, system integration between the demand for nickel products and the process of supplying raw materials urgently needed to support nickel processing. Therefore, this study aims to estimate the amount of raw materials and scheduling the availability of raw materials with applying the Material Requirement Planning. Furthermore, to find out the differences in the strategy of ordering raw materials in the system. Order fulfillment strategies (lot sizing) used are level, modified level, and dynamic lot sizing. The level strategy, as the initial strategy of the company, is a strategy that uses inventory as a support with labor made steady and demand is met from inventory. Modified level strategy are formulated to adjust level ordering in dynamic time. The dynamic lot sizing is a strategy of dynamic order quantity and dynamic time order. As for the analysis. The initial level strategy ,that simulate with several equations, shows some overstock and understock condition in the nickel production and material inventory. Its resulted in higher total cost and unfulfill nickel production. The formulation of modified level strategy and dynamic lot sizing can fulfill the material demand with lower total cost.